Penguatan Kapasitas Pengelolaan Naskah Kuno melalui Sosialisasi Identifikasi dan Pendaftaran di Perpustakaan Daerah - Kasim, Sunardy; Syamsurrijal, Syamsurrijal; Rachman, Dedy Febry; Marzuki, Khairan (Insan Kreasi Media, 2025)
This community service programme was implemented in collaboration with the Central Lombok Regional Library to address the limited capacity in managing ancient manuscripts, an important form of Sasak documentary heritage. To date, manuscripts written on palm leaves, daluang, and paper containing texts such as babad, serat, and suluk have not been systematically documented and lack standardised cataloguing practices. This situation restricts research access, increases the physical vulnerability of the materials, and weakens the connection between local collections and wider manuscript information networks at regional and national levels. Responding to this urgency, the programme focused on strengthening local knowledge preservation while enhancing institutional capability in written heritage management. Activities were designed through a Participatory Action Research (PAR) approach, involving needs assessments, focus group discussions, manuscript identification workshops, simulations of standard metadata application, and guided assistance in developing an initial inventory. Librarians, local collection managers, and manuscript owners were actively engaged as partners throughout the process. The programme’s outcomes demonstrated a significant improvement in participants’ understanding of manuscript characteristics, identification methods, and cataloguing techniques. Moreover, a registration workflow and a dedicated management team were established to ensure future continuity. These results illustrate that participatory capacity building is an effective strategy for improving local manuscript management and supporting the long-term preservation of Sasak cultural heritage